2016
DOI: 10.1111/ijfs.13176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of black coffee temperature profiles consumed from paper‐based cups and effect on affective and descriptive product sensory attributes

Abstract: Summary Sensory acceptance testing was used to determine whether the serving temperature of black filter coffee had an effect on the hedonic sensory quality of the imbibed product using naïve assessors (n = 25) analysed in duplicate. Additionally, descriptive sensory evaluation was used to assess coffee aroma, flavour and aftertaste attributes at different temperatures using a total of fourteen attributes. Prior to consumption, exothermic spectral analysis was assessed using a thermal imaging camera on each cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…The results from this study showed the dynamics of sensory attributes in both coffee and green tea samples with respect to serving temperatures of 65, 25, and 5 • C. Six and 18 sensory attributes of coffee and green tea samples, respectively, significantly differed in terms of sample temperature. Sample temperature-induced changes in sensory attributes of brewed coffee have been also observed in other studies (Stokes et al, 2016;Steen et al, 2017). In a recent study conducted by Stokes et al (2016), "coffee flavor, " "roasted/burnt flavor, " and "full body" attributes were more associated with brewed coffee samples evaluated at higher temperatures of 60.4, 70.8, and 74.4 • C, while "earthy flavor" and "sour/acidic taste" were more related to those evaluated at lower temperatures of 31.0 and 41.1 • C. The present study to some extent showed similar results, that "roasted flavor" attribute of brewed coffee was more often identified at higher temperature (65 • C), while "pungent aroma, " "metallic flavor, " and "skunky flavor" attributes were more often characterized at lower temperature (5 • C).…”
Section: Variations With Respect To Emotional Responses and Sensory Asupporting
confidence: 80%
See 1 more Smart Citation
“…The results from this study showed the dynamics of sensory attributes in both coffee and green tea samples with respect to serving temperatures of 65, 25, and 5 • C. Six and 18 sensory attributes of coffee and green tea samples, respectively, significantly differed in terms of sample temperature. Sample temperature-induced changes in sensory attributes of brewed coffee have been also observed in other studies (Stokes et al, 2016;Steen et al, 2017). In a recent study conducted by Stokes et al (2016), "coffee flavor, " "roasted/burnt flavor, " and "full body" attributes were more associated with brewed coffee samples evaluated at higher temperatures of 60.4, 70.8, and 74.4 • C, while "earthy flavor" and "sour/acidic taste" were more related to those evaluated at lower temperatures of 31.0 and 41.1 • C. The present study to some extent showed similar results, that "roasted flavor" attribute of brewed coffee was more often identified at higher temperature (65 • C), while "pungent aroma, " "metallic flavor, " and "skunky flavor" attributes were more often characterized at lower temperature (5 • C).…”
Section: Variations With Respect To Emotional Responses and Sensory Asupporting
confidence: 80%
“…Four research propositions were tested in this study. First, it was to be determined whether specific sensory attributes of coffee or green tea samples would be more detectable or dominant at hot, ambient, or cold temperatures (Research proposition 1), based on previous research regarding the effects of serving temperatures on intensities of sensory attributes in basic taste solutions, foods, and beverages (Moskowitz, 1973;Zellner et al, 1988;Ross and Weller, 2008;Kim et al, 2015;Lipscomb et al, 2016;Stokes et al, 2016;Steen et al, 2017). Due to temperaturedependent variations with respect to perceived intensity, certain attributes may be more dominant in coffee or green tea samples at hot, ambient, or cold temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research conducted comparing wet and dry aged beef has been undertaken using assessors ([1] n = 77, [7] n = 80 -91) and the research comparing these ageing regimes to those incorporating moisture permeable bags and bone-in samples have used trained panellists [9] n = 6; [10], n = 6. Sensory Acceptance Testing is a hedonic sensory methods used to determine the degree to which products are liked and has been applied to various product including meats [11]- [17], dairy products [18]- [29], salads, [30] [31], Bakery products [32] [33] and beverages [34] [35] [36] [37] [38]. Thus the objective of the present Food and Nutrition Sciences study was to directly compare the sensory acceptability, using sensory acceptance testing, of traditional bone-in dry aging to de-boned dry aged loins and de-boned dry aged loins in moisture permeable bags (dry-ageing bag), in the same study.…”
mentioning
confidence: 99%
“…Most-preferred/recommended temperature°C (°F) Borchgrevink et al (1999) 68.3°C (155°F) Pipatsattayanuwong et al (2001) 71.4°C (161.8°F) Lee and Mahoney (2002) 59.8°C (139.6°F) Brown and Diller (2008) 57.8°C (136°F). Stokes et al (2016) 70.8°C (159.4°F) Dirler et al (2018) 63°C (145°F) mixing technique from Lee and O'Mahony (2003) was adopted. Both the preferred temperature and the pain threshold were noted.…”
Section: Studymentioning
confidence: 99%